PENGARUH STATUS SOSIAL EKONOMI ORANG TUA DAN MOTIVASI BELAJAR TERHADAP HASIL BELAJAR KOGNITIF KEWIRAUSAHAAN PADA SISWA KELAS XI SMK KRISTEN 1 SURAKARTA TAHUN AJARAN 2017/2018 - -, Setyo Dwi Utomo -; -, Bambang Wasito Adi -; -, Sunarto - (Jurnal Pendidikan Bisnis dan Ekonomi, 2018)
This research aims to know: (1) the effect of parental socio-economic status and learning motivation towards cognitive student achievement of entrepreneurship education on student grade XI of Vocational High School Kristen 1 Surakarta, (2) the effect of parental socio-economic status towards cognitive student achievement of entrepreneurship education on student grade XI of Vocational High School Kristen 1 Surakarta, (3) the effect of learning motivation towards cognitive student achievement of entrepreneurship education on student grade XI of Vocational High School Kristen 1 Surakarta. The object of this research is student grade XI in Vocational High School Kristen 1 Surakarta which is get entrepreneurhip education which amounting to 119 students. The sampling techinique used proportional random sampling which amounted to 55 students. Questionnaires and documentation are used as data collection tools. Questionnaires are used to collect data of parental socio-economic status and learning motivation, while documentation is used to collect data on results student avhievement of entrepreneurship education. Data analysis techniques used Regression test. The results of this research are (1) there is a significant effect of parental socio-economic status and learning motivation towards student achievement of entrepreneurship education on student grade XI of Vocational High School Kristen 1 Surakarta with the result of count Fcount>Ftable (97,943 > 3,18) (2) there is a significant effect the effect of parental socio-economic status towards student achievement of entrepreneurship education on student grade XI of Vocational High School Kristen 1 Surakarta with the result of count ttest>ttable (4,108 > 2,006) and significance 0,000 < 0,05 (3) there is a significance effect of learning motivation towards student achievement of entrepreneurship education on student grade XI of Vocational High School Kristen 1 Surakarta with the result of count ttest>ttable (7,134 >2,006) and significance 0,000 < 0,05.